KELAYAKAN MEDIA FLIPBOOK PADA SUBMATERI KONSEP KEANEKARAGAMAN HAYATI DI SMA KELAS X - Arista, Heni; Syamswisna, Syamswisna; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLearning media a tool that functions and used for learning messages, learning media can clarify the presentation of messages and information so as to facilitate and improve learning processes and outcomes. This study aims to determine the feasibility of flipbook media in the submission of biodiversity concepts in class X high school. The method used in the research descriptive method with purposive sampling technique. The instrument used in this study the media validation sheet and for data analysis using the CVI formula. There are 7 aspects measured in the validation sheet, namely consistency, format, content, organization, attractiveness, font size and empty space. Flipbook media validation carried out by 5 validators consisting of 2 lecturers of Biology Education FKIP Tanjungpura University and 3 Biology Teachers of high school class X in Sadaniang District. the results of media validation received a CVI value of 0.99 and flipbook media was declared feasible to be used as a learning media in class X high school in the biodiversity concept submission.Keywords :Flipbook, Kelayakan, Konsep keanekaragaman hayati.